How shift work influences anxiety, depression, stress and insomnia conditions in Italian nurses: an exploratory study: Shift work in Italian nurses - Vitale, Elsa; Lupo, Roberto; Artioli, Giovanna; Mea, Rocco; Lezzi, Pierluigi; Conte, Luana; De Nunzio, Giorgio (Acta Biomedica Atenei Parmensis, 2023)
Background and aim of the work. Evidence suggested that the nursing profession could be considered as a very complex profession also for nurses themselves. To investigate how shift work influence nurses’ health also considering anxiety, depression, stress and insomnia conditions. Methods. An on-line cohort observational study was conducted during May 2022 to 408 nurses. Results. 408 nurses were on-line recruited. Most of the nurses recruited worked also during the night shift (73.3%) and were very young (p<0.001), as aged less than 30 years (29.2%) and also aged between 31-40 years (29), too. Significant difference was reported in smoking habit, as nurses who worked also during the night reported higher smoking habit then the others (p=0.020). None further significant differences according to sex, age, work experience, nursing education, nursing activity, BMI and shift work was found. Finally, none differences were assessed between anxiety, depression, stress and insomnia conditions according to shift work typologies. Conclusions. The present study discussed research results already highlighted in the current literature; however, it collected further information and assessed additional differences, so that a more complete picture of the nursing profession could be defined.